2012
DOI: 10.1002/tea.21024
|View full text |Cite
|
Sign up to set email alerts
|

A learning progression for water in socio‐ecological systems

Abstract: Providing model‐based accounts (explanations and predictions) of water and substances in water moving through environmental systems is an important practice for environmental science literacy and necessary for citizens confronting global and local water quantity and quality issues. In this article we present a learning progression for water in environmental systems for students in elementary through high school grades. We investigated student accounts of water and substances in water moving through atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 54 publications
2
127
0
2
Order By: Relevance
“…From there, the initial LP hypothesis can be further developed either with cross-age samples (e.g. Gunckel, Covitt, Salinas, & Anderson, 2012;Mayes et al, 2014) or in the context of instruction (e.g. Shea & Duncan, 2013;Yin, Tomita, & Shavelson, 2014).…”
Section: Lp Frameworkmentioning
confidence: 99%
“…From there, the initial LP hypothesis can be further developed either with cross-age samples (e.g. Gunckel, Covitt, Salinas, & Anderson, 2012;Mayes et al, 2014) or in the context of instruction (e.g. Shea & Duncan, 2013;Yin, Tomita, & Shavelson, 2014).…”
Section: Lp Frameworkmentioning
confidence: 99%
“…Learning progressions are delineated by an upper and a lower anchor (Gunckel, Covitt, Salinas, & Anderson, 2012). Students' tentative understanding of a particular idea or concept upon entering the learning progression defines the lower anchor (Neumann, Viering, Boone, & Fischer, 2013).…”
Section: Specifying Construct Stagementioning
confidence: 99%
“…The methodology of Jin and Anderson's (2012) study was used by many others on learning progression. Using a similar method, Gunckel, Covitt, Salinas, & Anderson (2012) conducted a learning progression study on the concept of water in socio-ecological systems, targeting citizen participation in handling prevalent water problems. Their findings suggested that some changes in the curriculum, assessments, and interventions could be conducted to distinguish students' performances into four levels.…”
mentioning
confidence: 99%
“…The significance of sound understanding of environmental problems becomes central for citizen participation in addressing issues stemming from human interference with natural systems (Mohan et al, 2009;Gunckel et al, 2012). Therefore, in order to gain agency in evidence-based decisionmaking on environment-related issues from a scientific perspective, students need to develop understanding of causal relationships among entities implicated in the negative impact of the agricultural production on ecological systems (Gunckel et al, 2012;Williamson, 2011).…”
Section: Attendance To Critical Features During the Development Of Agmentioning
confidence: 99%
“…The overarching goal of the curricular unit aims to emphasize causal relations among entities implicated in the agricultural impact on the environment. As a result of this coherent curricular sequence, ecology high school students establish evidence-based causal relations among entities in mapping out connection between nitrogen and carbon cycles as a mechanism implicated in the impact of intensive agriculture on ecological systems (Mohan et al, 2009;Gunckel et al, 2012;Williamson, 2011). Such an approach intends to facilitate students' understanding of lower level activities and encourage students to use causal relations to construct evidence-based explanation about higher-level observable phenomenon (Williamson, 2011).…”
Section: Coherent Storyline In Research-based Unitmentioning
confidence: 99%